THE EFFECTS OF DETRAINING PHYSICAL ABILITIES IN THE ELDERLY. (Fiep Bulletin - online, 2012)
The growth of the elderly population is a worldwide phenomenon. As a result the elderly occupies a prominent role in society. Currently, health professionals stress the importance of physical activity as a factor in the success of the aging process. This phenomenon is marked by a process of loss of functionality caused by a significant drop in performance in physical and functional capabilities. In order to avoid such losses indicate the health of the elderly doing physical exercise, and one of the most widely shown today is resistance exercise (RE). RE allows the body to appropriate improvements and improvements in physical abilities. However, such changes induced by regular physical activity can be reduced or return the situation prior to the training program when the exercise is stopped, and this phenomenon is called untrained. This work aims to determine the effects of disruption of an RE program on the physical capabilities, specifically the flexibility, strength of upper and lower limbs and resistance, in the elderly, 60 to 82 years participating in the project "Health and Quality of Life "Laboratory of resistance exercise you read. To assess the physical abilities of the elderly were performed the following tests: flexibility (Wells Bench), stationary motion, hand grip (hand dynamometer), and sit ups. These are effected in three periods, at the end of the program RE, after fifteen days of the first tests was the second evaluation and third evaluation shortly after forty-five days. The analyzed group consisted of 19 elderly. According to the statistical analysis results in a reduction in the first place for the third time, demonstrating that the detraining was deleterious to the mentioned variables. However, these reductions do not cause significant drops in the statistical point of view. It is concluded that periods of 15 to 45 days did not promote significant losses in terms of the statistical variables. But noted that the reversal occurred, so the principle of continuity is reinforced by the results of this study.
Keywords: Elderly; Physical abilities; Untrained